International space law and norms: an approach for assessing compliance - Lindgren, David (Department of Electrical Engineering, 2020)
The number and types of space activities and space actors continue to increase, posing new and unique challenges for space governance and policy. Presently, a comprehensive, periodic, and systematic measure of states’ efforts to comply with existing international space law and norms does not exist, suggesting a critical need to ensure robust and informed policymaking as space activities and actors increase. The evidence-based policymaking and programming movement, alongside the rise of ratings and rankings research, suggest the utility of such an assessment to informing policymaking and identifying compliance or partial or noncompliance of spacefaring countries. Numerous ratings and rankings assessments measure country-level trends across various sectors, including but not limited to business, democracy, economics, human rights, governance, and prosperity. However, none currently measure the behaviour and policies of countries regarding the exploration and use of outer space. An annual space report, published by the Space Security Index, does provide an overview of space activities and trends according to various thematic areas, but neither provides a historical nor baseline comparison of states’ behaviour. This dissertation endeavours to propose a set of criteria, grounded in international space treaties and United Nations-level principles, resolutions, and guidelines, for which space policy stakeholders can apply to countries and develop a comparative understanding of their levels of compliance with binding international space law and non-binding space norms.